2019
DOI: 10.3389/fnins.2019.00327
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Cognitive Dysfunction in Postural Tachycardia Syndrome After Rapid Water Drinking

Abstract: Background: Postural tachycardia syndrome (POTS) is a form of autonomic dysregulation and is characterized by an excessive heart rate (HR) increment upon the upright body position while blood pressure is maintained. Patients experience typical symptoms of orthostatic intolerance such as dizziness, nausea and cognitive impairments. The present study assessed position-dependent attentional and cognitive functioning in POTS patients compared to healthy subjects and tested the response of cognitive perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Compared with control or reference populations, SF-36 and RAND-36 physical and mental health summary scores were significantly reduced in patients with VVS ( 10 , 28 ). In patients with POTS, one study using the SF-36 showed that both physical and mental health summary scores were reduced compared to healthy controls ( 46 ), while two others found only the physical component summary score to be impaired ( 41 , 43 ). In a study using the RAND-36, both physical and mental health composite scores were impaired in patients with POTS, however the deficits in the physical health composite score were much larger than in the mental health composite score ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with control or reference populations, SF-36 and RAND-36 physical and mental health summary scores were significantly reduced in patients with VVS ( 10 , 28 ). In patients with POTS, one study using the SF-36 showed that both physical and mental health summary scores were reduced compared to healthy controls ( 46 ), while two others found only the physical component summary score to be impaired ( 41 , 43 ). In a study using the RAND-36, both physical and mental health composite scores were impaired in patients with POTS, however the deficits in the physical health composite score were much larger than in the mental health composite score ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“… Meta-analysis of SF-36 summary scores in patients with VVS and POTS compared to normative data. Physical (A) and mental (B) component summary scores are shown for patients with VVS ( 27 30 , 56 ) (red) and POTS ( 41 , 43 46 ) (blue). Data for each study are presented as the mean (circle) and standard deviation (whiskers) with the size of the circle proportional to the study sample size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was still unclear whether improvements in classic OI symptoms translated to improvement in cognitive symptoms in patients with POTS. To address these questions, Rodriguez and colleagues recently published their study, "Orthostatic cognitive dysfunction in postural tachycardia syndrome after rapid water drinking," in Frontiers in Neuroscience [10]. To understand the degree of orthostatic cognitive impairment and its response to rapid water drinking, the researchers recruited eight patients with neuropathic POTS and compared them to eight age-and sex-matched healthy controls.…”
Section: Brain Fog In Postural Tachycardia Syndrome Responds To Rapidmentioning
confidence: 99%
“…1,2 Patients with POTS experience symptoms of orthostatic intolerance in the upright position such as lightheadedness, dizziness, palpitations, tremulousness, generalized weakness and leg pain, blurred vision, dyspnea, nausea, headache and cognitive dysfunction. [3][4][5][6] Many patients with POTS additionally report non-orthostatic symptoms of autonomic origin such as fatigue, gastrointestinal complaints, sleep disturbances, restless legs symptoms and exercise intolerance. 7,8 The exact etiology of POTS is still unknown, although in recent years evidence has accumulated that in a subset of patients with POTS the pathogenesis of dysautonomia may be immune-mediated.…”
Section: Introductionmentioning
confidence: 99%